Intramembrane protease PARL defines a negative regulator of PINK1- and PARK2/Parkin-dependent mitophagy - Meißner, Cathrin; Lorenz, Holger; Geiger, Beate; Lemberg, Marius (Autophagy, 2015)
Mutations in PINK1 and PARK2/Parkin are a main risk factor for familial Parkinson disease. While the physiological mechanism of their activation is unclear, these proteins have been shown in tissue culture cells to serve as a key trigger for autophagy of depolarized mitochondria. Here we show that ablation of the mitochondrial rhomboid protease PARL leads to retrograde translocation of an intermembrane space-bridging PINK1 import intermediate. Subsequently, it is rerouted to the outer membrane in order to recruit PARK2, which phenocopies mitophagy induction by uncoupling agents. Consistent with a role of this retrograde translocation mechanism in neurodegenerative disease, we show that pathogenic PINK1 mutants which are not cleaved by PARL affect PINK1 kinase activity and the ability to induce PARK2-mediated mitophagy. Altogether we suggest that PARL is an important intrinsic player in mitochondrial quality control, a system substantially impaired in Parkinson disease as indicated by reduced removal of damaged mitochondria in affected patients.
Gesehen am 12.06.2020